Examining the factors contributing customer satisfaction: a case study of Prudential BSN Takaful Berhad, Al Isra Johor / Siti Aishah Abdullah, Siti Nor Shageera Md Nasir and Sulaiman Mohamed Taib - Abdullah, Siti Aishah (2018)
This dissertation examines the factors that contribute to the satisfaction of Prudential BSN Takaful Berhad, Al Isra Johor' customers in order to suggest Al Isra Johor' agents some recommendations to achieve better persistency ratio. Many researches have been done generally on service quality in service industry accepting that customer satisfaction and customer retention has strong relationship. However, little research has been done regarding the factors that contribute to the customer satisfaction in takaful business specifically, hence, it is very crucial to study the factors that contribute to the customer satisfaction since customer retention rate (persistency ratio) is very important to insurance or takaful agents for their sustainability in the industry. It is the objectives of this paper to assess reliability, responsiveness, assurance and empathy of SERVQUAL model to examine which are the factors that crucial for customer satisfaction. A survey on 130 existing clients of Al Isra Johor' agents were conducted and the result showed that reliability, responsiveness, and empathy are the three significant factors in contributing customers' satisfaction. The other one factor which is assurance is not significantly affecting customers' satisfaction. Other than the survey, an interview with on of Al Isra Johor' unit manager was conducted and internal documents from the organization were collected to enable the researchers to fully understand the environment that Al Isra Johor operates. Overall, based on the analysis outcome, the researchers highly recommend that Al Isra Johor allocates more resources into improving their agents' skillsets in servicing including after-sales service in order to ensure that customers can have maximum satisfaction towards the service provided